Identifying Worst-Case Test Vectors for Delay Failures Induced by Total Dose in Flash- based FPGA - Ammar, Adel (AUC Knowledge Fountain, 2015)
A thesis presented on the effects of space radiation on the flash-based FPGA leading to failure with applying a proposed fault model to identify the worst, nominal and best-case test vectors for each. This thesis analyzed the delay failure induced in a flash-based field programmable gate array (FPGA) by a total-ionizing dose. It then identified the different factors contributing to the amount of delay induced by the total dose in the FPGA. A novel fault model for delay failure in FPGA was developed. This fault model was used to identify worst-case test vectors for delay failures induced in FPGA devices exposed to a total ionizing dose. The fault model and the methodology for identifying worst-case test vectors WCTV were validated using Micro-semi ProASIC3 FPGA and Cobalt 60 radiation facility.